Proper names in Magda Gessler’s Kitchen Revolutions: Their functioning, motivation, naming practice - Siwiec, Adam (Papers in Linguistics, 2020)
The study is concerned with names of restaurants and other eateries, considered to be important elements of the media text, contributing to the understanding of that type of text. They include primarily nomenclature that makes up the linguistic landscape of the TV show Kitchen Revolutions, influencing the linguistic portrayal of reality and the dramatic narrative of the story which is told in the show. They are often replaced with novel names made up by the show host, Magda Gessler, which allow the restaurants to begin a new life on the market. It is those names that undergo special scrutiny in the study, in their semantic-motivational aspect and functional-pragmatic function (i.e. promotional goals), as elements of the titular “revolutions” and components of a successful business enterprise. The collected data show that we are dealing here with several possibilities, both at the formal level and with regard to the use of particular content. The naming practices presented in the show reveal a dominant pattern of naming, motivated by convention, which is based on the concept of a given place, with its services and products. In line with the culturally and socially dominant view of a given restaurant, the majority of naming acts performed in the show result in names of “things to eat” which point to what can be found on the menu.